Full-stack web development with GraphQl and React : build scalable full-stack applications with React 18 while learning to solve complex problems with GraphQl /: build scalable full-stack applications with React 18 while learning to solve complex problems with GraphQl. (2021) - Grebe, Sebastian
No abstract available